A Greigite-Based Magnetostratigraphic Time Frame for the Late Miocene to Recent DSDP Leg 42B Cores from the Black Sea - van Baak, Christiaan G. C.; Vasiliev, Iuliana; Palcu, Dan V.; Dekkers, Mark J.; Krijgsman, Wout (Frontiers in Earth Science, 2016)
Throughout the Late Neogene, the Black Sea experienced large paleoenvironmental changes, switching between (anoxic) marine conditions when connected to the Mediterranean Sea and (oxic) freshwater conditions at times of isolation. We create a magnetostratigraphic time frame for three sites drilled during Deep Sea Drilling Project (DSDP) Leg 42B to the Black Sea (drilled in 1975). At the time, magnetostratigraphic dating was impossible because of the presence of the little understood iron sulfide mineral greigite (in sediments a precursor to pyrite) as magnetic carrier. Our rock-magnetic results indicate that only anoxic conditions result in poor magnetic signal, likely as a result of pyrite formation in the water column rather than in the sediment. The magnetostratigraphic results indicate that Hole 379A, drilled in the basin center, has a continuous sedimentary record dating back to 1.3 Ma. Hole 380/380A is subdivided into three consistent intervals, 0-700 mbsf, 700-860 mbsf and 860-1075 mbsf. The top unit covers the Pleistocene but the magnetostratigraphy is likely compromised by the presence of mass transport deposits. The middle unit spans between 4.3 and 6.1 Ma and records continuous deposition at ~10 cm/kyr. The lower unit lacks the independent age constraints to correlate the obtained magnetostratigraphy. Hole 381 is drilled on the Bosporus slope and as a result, hiatuses are common. A correlation to the nearby Hole 380/380A is proposed, but indicates deposits cannot straightforwardly be traced across the slope. Our improved age model does not support the original interpretation based on these cores of a desiccation of the Black Sea during the Messinian salinity crisis.